PENGARUH PENGGUNAAN PETA KONSEP TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS - Raisah Mardhiyati Labibah; Tias Ernawati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study descriptively aims to determine the tendency of science learning achievement and the critical thinking skill of students who were thought using concept maps and direct instruction models. Comparatively to know the difference of science learning VII grade students of SMP Negeri 12 Yogyakarta were learned using concept map and direct instruction achievement model viewed from critical thinking skill. The research is a quasi experiment. The data were collected by documentation, test, and questionnaire. Comparatively, there is a significant difference of science learning achievement between learning using concept maps and direct instruction model. The average score of science learning achievement and critical thinking skills using concept maps is higher than the direct instruction model, so there is an effect of using concept maps on science learning achievement based on students critical thinking skills VII grade students of SMP Negeri 12 Yogyakarta.